Simple, inexpensive way of fabricating high quality Zn(O)S nanoparticles by varying pH. (1st June 2018) - Dwivedi, Deepak; Patel, Tvarit A.; Panda, Emila
Abstract: In this work, a simple, inexpensive room temperature chemical bath deposition is proposed to synthesize high-quality Zn(O)S nanoparticles of varied composition. The band gap of these nanoparticles is found to alter by varying their chemical composition. Through this study, the formation of quantum confined ZnS and ZnOS nanoparticles as a function of p H is confirmed. A possible mechanism for the formation of these nanoparticles with respect to p H is discussed here.